Putusan Mahkamah Agung no 195 K/MIL/2015 mengenai Menghilangkan barang keperluan perang ditinjau BERDASARKAN Pasal 148 Kitab Undang-Undang Hukum Pidana Militer DAN PERSPEKTIF HUKUM HUMANITER: SUPREME COURT DECISION NO. 195 K/MIL/2015 REGARDING THE LOSS OF WAR SUPPLIES REVIEWED BASED ON ARTICLE 148 OF THE MILITARY CRIMINAL CODE AND HUMANITARIAN LAW PERSPECTIVE - Rahmawati, Nuraida; Ramadan, Nursyachrani Tiara; Wangga, Maria Silvya E. (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2024)
Taking military equipment as a firearm is a crime, and soldiers who carry firearms illegally will be punished according to criminal law. This study aims to determine and apply its nature, the study of the purpose of law, values, definitions, validity of legal rules, legal concepts and legal methods. The approach used in this study is a legal approach, historical approach, and theoretical approach. The formulation of this research problem is as follows. 1) What are the types of diseases that can arise as a result of taking up arms in decision-making? 2) What punishment will be given to perpetrators of crimes taking up arms under international humanitarian law? 3) What is the legal perspective used in the context of international humanitarian law? From the findings, one of the events of the loss of property or weapons involving TNI members was led by Budi Santoso, Lieutenant Colonel of Yonarmed unit 18/105 Magetan in East Java. Conclusion of Medan Military High Court Lieutenant Sus Budi Santosa, SH., MH. (March 5, 2018) the results showed that if a missing weapon is found, the soldier will be tried based on the crime he committed. The study is expected to focus on the necessary sanctions to prevent a recurrence of something similar in the future.